Zero Rating and Net Neutrality in Brazil’s Internet Legal Framework: Digital Inclusion and Development of New Technologies - Erhardt, André (Law, State and Telecommunications Review, 2016)
Purpose ”“ This article discusses the effects of zero rating on the principle of network neutrality and social and technological transformations of Brazil. Methodology/approach/design ”“ It was composed from bibliographic research and data collection in order to explain the practice of zero rating, framing it in the theory formulated by Ernest J. Wilson. Findings ”“ The article presents in details the offer of mobile internet service in Brazil and evaluates zero rating under the legislation and its impact on digital inclusion and technological development. Practical implications ”“ The article serves as an invitation to the researcher interested in the social economic implications of zero rating and its regulation. Originality/value ”“ It innovates in the Brazilian legal research presenting a peculiar approach on the model proposed by Ernest J. Wilson analyzing social transformations on par with technological development.